2016
DOI: 10.1016/j.bbadis.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Mixed – Lineage Protein kinases (MLKs) in inflammation, metabolism, and other disease states

Abstract: Mixed lineage kinases, or MLKs, are members of the MAP kinase kinase kinase (MAP3K) family, which were originally identified among the activators of the major stress-dependent mitogen activated protein kinases (MAPKs), JNK and p38. During stress, the activation of JNK and p38 kinases targets several essential downstream substrates that react in a specific manner to the unique stressor and thus determine the fate of the cell in response to a particular challenge. Recently, the MLK family was identified as a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 81 publications
0
42
0
Order By: Relevance
“…JNKs are specifically activated by two dual‐specificity MAP kinase kinases (MKKs), namely, MKK4 and MKK7, through phosphorylation of threonine and tyrosine . Similar to the activation of JNK, MKK4 and MKK7 are phosphorylated in their activation by upstream MAP kinase kinase kinases (MKKKs), including mixed lineage kinase (MLK)‐1‐4, DLK, TAK1, ASK1, LZK and ZAK . Recently, it was demonstrated that MLK3 silencing or MLK inhibition blocks JNK activation and both GBM cell migration and invasion, and silencing MLK4 suppresses self‐renewal, motility and radio‐resistance of glioma stem cells, suggesting that the MLK‐JNK axis is crucial for GBM tumourigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…JNKs are specifically activated by two dual‐specificity MAP kinase kinases (MKKs), namely, MKK4 and MKK7, through phosphorylation of threonine and tyrosine . Similar to the activation of JNK, MKK4 and MKK7 are phosphorylated in their activation by upstream MAP kinase kinase kinases (MKKKs), including mixed lineage kinase (MLK)‐1‐4, DLK, TAK1, ASK1, LZK and ZAK . Recently, it was demonstrated that MLK3 silencing or MLK inhibition blocks JNK activation and both GBM cell migration and invasion, and silencing MLK4 suppresses self‐renewal, motility and radio‐resistance of glioma stem cells, suggesting that the MLK‐JNK axis is crucial for GBM tumourigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…A set of sequentially-activated kinases comprise the core of the JNK signaling pathway, a developmentally regulated pathway that is also activated in response to stress signals [ 61 63 ]. JNK activity influences the establishment of planar polarity in the fly retina [ 64 ], but otherwise does not contribute significantly to eye development [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…It located in the SH3 domain of MAP3K21, which was responsible for controlling or regulating protein-protein interactions in the signal transduction pathways, such as cytoplasmic signaling (Koch, Anderson, Moran, Ellis, & Pawson, 1991;Schlessinger, 1994). MAP3K21 is a member of the mixed lineage kinases family that acts as a specific modulator to inhibit lipopolysaccharide (LPS)-induced activation of c-Jun N-terminal kinase (JNK), or extracellular signal-regulated kinase (ERK) (Craige, Reif, & Kant, 2016), or as a negative regulator of Tolllike receptor 4 (TLR4) signaling (Seit-Nebi, Cheng, Xu, & Han, 2012). It's well known that JNK, ERK, and TLR4 are all implicated with obesity through elevating gene expression level (Ahmad et al, 2012;Hirosumi et al, 2002), promoting insulin resistance (Hirosumi et al, 2002;Ozaki et al, 2016;Pal et al, 2012;Solinas & Becattini, 2017), or stimulating adipogenic differentiation (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%